Overcoming the Soviet Legacy in Land Surveying and Topographic-Geodetic Activities in Ukraine: Terminological Unification, Reframing of Scope and Institutional Integration - Martyn, A. (Land Management, Cadastre and Land Monitoring, 2025)
The article develops an integrated framework for overcoming post-Soviet inertia in the interaction between land management and topographic–geodetic activities in Ukraine. It demonstrates that the Soviet educational–professional tradition narrowed geodesy to measurement-centric engineering practices while marginalizing the European understanding of land management as a project- and law-driven activity that designs boundaries and regimes of land use with direct legal consequences. Drawing on international frameworks (FIG, CLGE, INSPIRE, LADM), current Ukrainian legislation, and the author’s long-term observation of professional debates on social media, the study substantiates: (1) the need for terminological unification (surveyor as a generic term, with clear distinctions between land/cadastral surveyor and engineering/topographic surveyor; geodesist is not a synonym for surveyor); (2) a reframing of functional roles whereby topographic–geodetic work is an infrastructural instrument enabling value creation across other sectors, whereas land management directly creates new real-estate objects and planning structures and governs asset value through RRR (rights–restrictions–responsibilities) approaches; and (3) institutional integration of data and processes based on INSPIRE/LADM semantic models. The paper identifies structural drivers of the perceived “crisis” after 1991—namely, the sharp decline of state demand for “centralized geodesy” and the technological automation of measurements (GNSS, satellite and aerial imagery, UAVs, GIS). It proposes the modernization of higher education under specialty G18 (“Geodesy and Land Management”) via interdisciplinary curricula (geodesy × land management × cadastre × spatial planning × real-estate valuation), the adoption of semantic data models and ethics with procedures ensuring public trust in boundaries, and sustained professional communication as a mechanism to eliminate legacy, Soviet-rooted conflicts between communities. Keywords: land management; geodesy; topographic-geodetic activities; cadastre; boundaries; RRR (rights-restrictions-responsibilities); INSPIRE; LADM; terminology harmonization; professional qualifications; NSDI; institutional integration; spatial planning; real-estate valuation.